Merkel cell carcinoma expresses the immunoregulatory ligand CD200 and induces immunosuppressive macrophages and regulatory T cells - Gaiser, Maria; Weis, Cleo-Aron Thias; Gaiser, Timo; Buder-Bakhaya, Kristina; Herpel, Esther; Warth, Arne (OncoImmunology, 2018)
Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer that responds to PD-1/PD-L1 immune checkpoint inhibitors. CD200 is another checkpoint modulator whose receptor is found on tumor-promoting myeloid cells, including M2 macrophages. We found high CD200 mRNA expression in MCC tumors, and CD200 immunostaining was demonstrated on 95.5% of MCC tumors. CD200R-expressing myeloid cells were present in the MCC tumor microenvironment. MCC-associated macrophages had a higher average CD163:CD68 staining ratio (2.67) than controls (1.13), indicating an immunosuppressive M2 phenotype. Accordingly, MCC tumors contained increased densities of FOXP3+ regulatory T-cells. Intravenous administration of blocking anti-CD200 antibody to MCC xenograft mice revealed specific targeting of drug to tumor. In conclusion, MCC are highly CD200 positive and associated with immunosuppressive M2 macrophages and regulatory T-cells. As anti-CD200 antibody effectively targets CD200 on MCC tumor cells in vivo, this treatment may provide a novel immunotherapy for MCC independent of PD-1/PD-L1 blockade.
Gesehen am 08.08.2019